2022
DOI: 10.1002/14651858.cd010216.pub7
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarettes for smoking cessation

Abstract: This review is published as a Cochrane Review in the Cochrane Database of Systematic Reviews 2022, 11. Cochrane Reviews are regularly updated as new evidence emerges and in response to comments and criticisms, and the Cochrane Database of Systematic Reviews should be consulted for the most recent version of the Review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
89
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 273 publications
5
89
1
3
Order By: Relevance
“…E-cigarettes have been the most used tobacco product among youth since 2014, and significant work is ongoing to address this concerning public health issue . Although growing evidence indicates that certain e-cigarettes may facilitate smoking cessation among adults, further high-quality research on this issue, including on short- and long-term clinical outcomes, is needed. Such research need not be mutually exclusive of ongoing efforts to rigorously prevent use of e-cigarettes by youth, increase use of effective cessation methods such as counseling and FDA-approved cessation medications, and explore other innovative approaches to assist adults to quit completely.…”
Section: Individual Levelmentioning
confidence: 99%
“…E-cigarettes have been the most used tobacco product among youth since 2014, and significant work is ongoing to address this concerning public health issue . Although growing evidence indicates that certain e-cigarettes may facilitate smoking cessation among adults, further high-quality research on this issue, including on short- and long-term clinical outcomes, is needed. Such research need not be mutually exclusive of ongoing efforts to rigorously prevent use of e-cigarettes by youth, increase use of effective cessation methods such as counseling and FDA-approved cessation medications, and explore other innovative approaches to assist adults to quit completely.…”
Section: Individual Levelmentioning
confidence: 99%
“…Vaping products in Great Britain can legally be sold only to those aged 18 years or older . Vaping can help some smokers to quit smoking . However, there is concern about youths’ use of vaping products, particularly with the recent increase in the use of disposable vaping products among youths younger than 18 years in Great Britain…”
Section: Introductionmentioning
confidence: 99%
“…This indicates a perception that e-cigarettes are effective smoking cessation tools [ 37 ] and healthier alternatives to smoking [ 18 , 38 ]. Recent meta-analyses on the efficacy of e-cigarette use in smoking cessation have provided inconclusive results [ 39 , 40 ]; however, a recent Cochrane review found there is “high-certainty evidence that ECs with nicotine increase quit rates compared to NRT and moderate-certainty evidence that they increase quit rates compared to ECs without nicotine” [ 41 ]. There are also data which suggest that tobacco smokers may substitute all or some of their cigarettes with e-cigarettes [ 42 ], supporting the perception by users that they are useful smoking cessation tools.…”
Section: Discussionmentioning
confidence: 99%